2021
DOI: 10.1136/jitc-2020-001498
|View full text |Cite|
|
Sign up to set email alerts
|

Dickkopf 1 impairs the tumor response to PD-1 blockade by inactivating CD8+ T cells in deficient mismatch repair colorectal cancer

Abstract: BackgroundDickkopf 1 (DKK1) is associated with tumor progression. However, whether DKK1 influences the tumor response to programmed cell death protein 1 (PD-1) blockade in colorectal cancers (CRCs) with deficient mismatch repair (dMMR) or microsatellite instability (MSI) has never been clarified.MethodsTumor tissues from 80 patients with dMMR CRC were evaluated for DKK1 expression and immune status via immunohistochemistry. Serum DKK1 was measured in another set of 43 patients who received PD-1 blockade therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…Another recent study indicated that elevated expression of DKK1 protein in mouse colorectal cancer (CRC) cells attenuated cytotoxicity of CD8 + T cells by decreasing T‐bet expression and activating GSK3β 36 . In this study, in patients with deficient mismatch repair (dMMR)/microsatellite instability (MSI) CRC, the increased‐serum DKK1 was related to poor prognosis, decreased sensitivity to PD‐1 blockade, and weakened immune status.…”
Section: Canonical Wnt Signaling and Dkk Family Proteins As Wnt Antag...mentioning
confidence: 71%
“…Another recent study indicated that elevated expression of DKK1 protein in mouse colorectal cancer (CRC) cells attenuated cytotoxicity of CD8 + T cells by decreasing T‐bet expression and activating GSK3β 36 . In this study, in patients with deficient mismatch repair (dMMR)/microsatellite instability (MSI) CRC, the increased‐serum DKK1 was related to poor prognosis, decreased sensitivity to PD‐1 blockade, and weakened immune status.…”
Section: Canonical Wnt Signaling and Dkk Family Proteins As Wnt Antag...mentioning
confidence: 71%
“…Those including REG1A, KLK8, KLK12 and MAGEA are up regulated in IVE group, among which REG1A and KLK8 predict poor prognosis in CRC [ 33 , 34 ], while silence of KLK12 and MAGEA can inhibit CRC growth and promote cell death [ 35 , 36 ]. Interestingly, cytoplasmic ASPN have been found to promote cell migration and indicate a poor prognosis in colorectal cancer [ 37 ], and elevated DKK1 expression is associated with recurrence and impairs the response to PD-1 blockade in dMMR CRC [ 38 ], while both of which are down regulated in IVE group. PTF1A has been well studied in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that DKK1 is contributed to the regulation of tumor immune cells. Sui et al reported that DKK 1 impairs the tumor response to PD-1 blockade by inactivating CD8 + T cells in colorectal cancer [14]. Another study demonstrated that metastatic castration-resistant prostate cancer (mCRPC) tumors with high DKK1 expression exhibit a CD8 + T-cell-poor tumor microenvironment in ltrated with immature M0 macrophages and M2 macrophages [31].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of DKK1 has recently emerged as a potential biomarker of cancer progression and prognosis for several types of malignancies [13]. A recent study reveals that DKK1 impairs the tumor response to PD-1 blockade by inactivating CD8 + T cells in defcient mismatch repair colorectal cancer [14]. Another study shows that upregulation of DKK1 could modulate anti-tumor immune populations within the tumor microenvironment by decreasing CD45 + leukocyte in ltration and reducing NK and CD8 + T cells [15].To summarize, DKK1 had immunoregulatory effects, including promoting Th2 cells response, reducing the functionality of T cells through MDSC modulation and suppressing the proliferation of CD8 + T cells and NK cells, thus contributing to in ammatory response and cancer immune evasion [16].Thus, further research of DKK1 in oncology has garnered a lot of attention.DKK1 has multifaceted functions in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%